NEUROPROTECTIVE EFFECT OF POLYHERBAL FORMULATION IN PARKINSON’S ANIMAL MODEL - NANDAGOPAl, ANITHA; ALI KHAN, MIR AMJAD (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The study is aimed to evaluate the antiparkinsonian effect of polyherbal formulation containing methanolic extract of Prunus amygdalus, Arachis hypogaea, and Citrullus lanatus (MEPAC) in chlorpromazine (CPZ)-induced Parkinson’s disease in Wistar albino rats. Methods: The antiparkinsonian activity of polyherbal formulation was studied in CPZ (3 mg/kg i.p.) induced Parkinson rat model. Rats were subjected to treatment with MEPAC and standard drug for a period of 21 days. The behavioral assessments, i.e., catalepsy and locomotor activity were assessed during the treatment period. Then animals were sacrificed, brains were isolated and homogenized for the estimation of biochemical parameters such as dopamine (DA), lipid peroxidation (LPO), glutathione (GSH), and superoxide dismutase (SOD). Histopathology of the brains was also done. Results: The cataleptic score of MEPAC (200 mg/kg and 400 mg/kg) treated rats was significantly reduced. On the other hand, there was improved in the locomotor activity. MEPAC (200 mg/kg and 400 mg/kg) treated rats showed increase in the level of DA, reduced GSH, SOD, and decreased LPO significantly. Conclusion: It may be concluded that methanolic extract of polyherbal formulation consisting of P. amygdalus, A. hypogaea, and C. lanatus showed a good antioxidant and neuroprotective effect in CPZ-induced Parkinson rats.